Manoeuvre load alleviation using multi-objective optimisation for combat aircraft wing. (26th August 2010) - Suresh, P.S.; Radhakrishnan, G.; Shankar, K.
The focus of the paper is to present the systematic approach for manoeuvre load alleviation (MLA) problem with multi-objective formulation and optimisation methods. MLA is a subset of active control technology (ACT) and deals with optimal rotation of control surfaces to effectively redistribute the forces on airframe. The mathematical model consists of flight control parameters as design variables, bending and twisting moment at the wing root as multiple independent conflicting fitness functions along with aircraft stability equations as equality constraints. By and large this MLA problem is addressed as single objective optimisation. The present work emphasises multi-objective problem formulation and presents the population based NSGA-II of multi-objective evolutionary algorithm (MOEA) as solution method. Symmetric manoeuvres with vertical acceleration load cases are optimised. The approach presented provides significant reduction of wing root bending and twisting moment through optimal ELEVator and aileron (ELEVON) rotations.